The European Union and culture : between economic regulation and European cultural policy - Littoz-Monnet, Annabelle, 1977- (European Policy Research Unit series., 2007)
Offers a fresh theoretical line in the field of European studies, pointing to the necessity of developing a dynamic multi-level approach, which captures the continuous interaction over time between EU level developments, national-level policies and the desire of all policy actors to further their interests and maximise their policy competencies.